2022
DOI: 10.3389/fenrg.2022.1007224
|View full text |Cite
|
Sign up to set email alerts
|

Study on the development options of tight sandstone oil reservoirs and their influencing factors

Abstract: The research area of tight sandstone oil reservoirs was selected, a numerical model of the oil reservoir was developed, and a study of the development options and influencing factors was carried out to analyze the influence of different development methods, physical and engineering parameters on the development dynamics. Study shows that the two main factors limiting the efficient development of tight sandstone reservoirs are reservoir properties and formation energy. Fractured horizontal well injection huff a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that the storage of tight oil in sandstones is dependent on the chemical composition of tight oil and the structural properties of the reservoir [5,[9][10][11][12]. Both the initial sediment composition and subsequent diagenetic modifications play a crucial role in determining a reservoir's properties [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the storage of tight oil in sandstones is dependent on the chemical composition of tight oil and the structural properties of the reservoir [5,[9][10][11][12]. Both the initial sediment composition and subsequent diagenetic modifications play a crucial role in determining a reservoir's properties [8,13].…”
Section: Introductionmentioning
confidence: 99%